Batch fermentation of corynebacterium glutamicum from sugarcane muscovado syrup for lysine production - Abrigo, C. S., Jr (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2001)
Lysine was produced from sugarcane muscovado syrup using flask cultures of Corynebacterium glutamicum and a 5-L batch fermentor. Optimum results were produced at an initial pH 7, aeration rate of 1.0 volume per minute, agitation rate of 25 rpm, and 60 g L⁻¹ sugar concentration. Based on the results of ANOVA, the parameters significantly affected lysine production.